Kalanchoe benbothae (K. subg. Fernandesiae; Crassulaceae subfam. Kalanchooideae), a new southern African species endemic to KwaZulu-Natal in the Maputaland-Pondoland Region of Endemism - Smith, Gideon F.; Crouch, Neil R. (Phytotaxa, 2021)
Since 2016 the number of species of Kalanchoe (Crassulaceae subfam. Kalanchooideae) known from southern Africa has increased by more than 50%, from 13 to 20. We here describe the 21st species known from the subcontinent. As far as could be determined, this new species, K. benbothae, is endemic to northeastern KwaZulu-Natal, the eastern-most province of South Africa, with the entire natural geographical distribution range of the species falling within the Maputaland-Pondoland Region of Endemism. Kalanchoe benbothae fits in K. subg. Fernandesiae, a cluster of species with large, paddle- to soup plate-sized leaves, and dense, elongated, often club-shaped inflorescences. The closest relative of K. benbothae is K. luciae, which was described just over 110 years ago, and was the second representative of K. subg. Fernandesiae to have been described. Kalanchoe benbothae differs from K. luciae mostly in its reproductive morphology (corolla lobe colour and orientation, anther colour and presentation, filament length, pistil shape, and size and shape of the nectar scales).